TEORI EMANASI MENURUT TOKOH FILSAFAT YUNANI DAN FILSAFAT ISLAM - Ahmad Ahmad (Sekolah Tinggi Agama Islam (STAI) Al-Wahliyah Barabai, 2022)
The philosophical basis of the concept of emanation is the desire to avoid God from a pluralistic nature in order to purify the oneness of God from all material things. The basic Islamic idea of God is His Oneness, His creation from nothingness and the dependence of all creation on Him. To prove the oneness of God, there is a term in philosophy called Emanation. Emanation in Greek philosophy is discussed like Thales who said everything comes from water, Platonists say that everything comes from reason (nous), reason itself comes from the One who thinks the most highly. while Aristotle based it on form and matter, both of which are related to motion driven by form which ends in a prime mover or God. Starting from this philosophical concept that gave birth to Islamic philosophers such as Al-Farabi, Ibn Sina, Ibn Maskawaih, and Suhrawardi Al-Maqtul